In vitro and in vivo evaluations of LB20304, a new fluoronaphthyridone. - Oh, J I (1996)
In vitro activity of LB20304 against 1,231 clinical isolates was evaluated and compared with those of ciprofloxacin, sparfloxacin, lomefloxacin, and ofloxacin. LB20304 demonstrated the most potent activity against gram-positive bacteria. It was 32- to 64-fold more active than ciprofloxacin against methicillin-susceptible Staphylococcus aureus, methicillin-resistant S. aureus, methicillin-resistant Staphylococcus epidermidis, and Streptococcus pneumoniae (penicillin G resistant). LB20304 was also highly active against most members of the family Enterobacteriaceae. Its activity was more potent than those of sparfloxacin, ofloxacin, and lomefloxacin and comparable to that of ciprofloxacin. The protective activities of LB20304 against systemic infections caused by gram-positive bacteria in mice were superior to those of ciprofloxacin and sparfloxacin. Against infections by gram-negative bacteria, LB20304 was slightly less active than ciprofloxacin.